3D PRINTING IN THE PREPARING OF FUTURE TEACHERS - KROTKY, Jan (Trends in education, 2014)
The author deals with current possibilities in prototyping, especially in education and training. Actual rapid development of techniques and technologies allows the adaptation of large and expensive equipment to create 3D models for use at home or at school. Teachers and educational institutions quickly react to these trends and prepare or have already implemented this technology in their teaching. This new uncharted area opens up next possibilities of the educational research, especially in the field of technical creativity.
Keywords: 3D printing; prototyping; technical creativity.